KORELASI EKSPRESI IMMUNOSITOKIMIA VASCULAR ENDOTHELIAL GROWTH FACTOR A (VEGF A) DENGAN PROTEIN GENE PRODUCT 9,5 (PGP 9,5) DARAH HAID PADA PATOFISIOLOGI ENDOMETRIOSIS - Dedy Hendry; Tita Husnitawati Madjid; Ruswana Anwar; Anita Rachmawati (Universitas Andalas, 2019)
There are changes of eutopic endometrium molecular fenotipe in endometriosis such as changes in gene expression, steroid hormone response, increase of inflammation marker and cellular adhesion molecule, decrease of apoptotic index and decidualization capacity, increase of oxidative stress marker, increase activity of angiogenesis and neurogenesis. This study was conducted to analyze the differences in the expression of angiogenic factors (VEGF A) and neurogenesis factors (PGP 9.5) eutopic endometrium of menstrual bleeding among patients with endometriosis and non endometriosis and then the correlation of the two factors. This study is a cross sectional that examines the relationship between the incidence of endometriosis with risk factors such as VEGF expression and PGP 9.5 in menstrual blood. There were significant differences in the expression of VEGF A eutopic endometrium menstrual blood between endometriosis and non endometriosis group (p=0.002). There are significant differences expression of VEGF A and PGP 9.5 eutopic endometrial of menstrual blood between endometriosis and non endometriosis groups. There is a positive correlation between the expression of VEGF A with PGP 9.5 eutopic endometrial of menstrual blood on endometriosis patients.Keywords: eutopic endometrium, menstrual blood, VEGF A expression, PGP 9.5 expression, immunocytochemistry